FUNDRAISING IN ACTION: HOW TO ENSURE THE SUCCESS OF A CROWDFUNDING CAMPAIGN? - Laureano, Raul M. S.; Trindade, G.; Abreu, M. Madalena; Santos, M-C.; Santos, M.; Silva, Tiago; Aquino, Itallo; Costa, Bárbara (IX International Congress on Teaching Cases related to Public and Nonprofit Marketing, 2017)
Coimbra Business School (ISCAC) wants to offer to five collaborators of nonprofit organizations the skills in fundraising practices by paying their tuition fees for them to enroll the Fundraising in Action course, a pioneer experience in Portugal. For this purpose, the ISCAC launched a crowdfunding project consistent with the recommendations established by the literature and also based on the results of a study carried out on a sample of 484 crowdfunding projects. The way to promote the project ans ensure the adherence of funders to the idea, somewhat utopian, raises a number of issues that need to be answered. In addition, the results of the data analyses do not provide clear clues as the way to act in order to maximize the probability of success to generate useful knowledge to the promoters. In short and because the outcome is unknown, if the Fundraising in Action is not going to be financed, other actions need to be implemented.